A longitudinal assessment of periodontal health status in 53 Labrador retrievers. (13th July 2018) - Wallis, C.; Patel, K. V.; Marshall, M.; Staunton, R.; Milella, L.; Harris, S.; Holcombe, L. J.
Abstract : Objectives: To determine the incidence and rates of progression of gingivitis and periodontitis in Labrador retrievers. Materials and Methods: Fifty‐three dogs, aged 1·1 to 5·9 years, had their periodontal health assessed every 6 months for up to 2 years. The extent of gingivitis and periodontitis was measured around the whole gingival margin of every tooth under general anaesthesia. Results: All dogs had gingivitis at the initial assessment. The majority (64·2%) of tooth aspects had very mild gingivitis. The palatal/lingual aspect of all tooth types was most likely to show bleeding when probed: 63·0% of these aspects had mild or moderate gingivitis. Over 2 years, 56·6% of dogs developed periodontitis and dogs as young as 1·9 years were affected. There was a significant positive correlation between the proportion of teeth with periodontitis and age. In total, 124 teeth (5·7%) developed periodontitis; 88 (71·0%) of these were incisors. The palatal/lingual aspect of the incisors developed the disease first (2·8% of incisor aspects). Clinical Significance: Periodontitis developed in regions that are difficult to see in conscious dogs implying that detection and treatment of disease requires periodic sedation or anaesthesia.